HUBUNGAN KONTEMPORER MALAYSIA–INDONESIA: TAHAP PENGETAHUAN DAN PEMAHAMAN GEN X DAN Y MALAYSIA - Ghani, Rohani Hj. Ab; Hamid, Ahmad Shukri bin Abdul; Paidi, Zulhilmi bin; Ratakrishnan, Mohan A/L; Mamat, Rashidah binti; Yeyeng, Andi Tenri (JPP (Jurnal Politik Profetik), 2021)
Looking at the relations between Malaysia-Indonesia, it could be seen that society has the power to direct the bilateral relations between two countries. In comparison, Indonesian society is more responsive than Malaysian society in responding to particular issues related to both countries. The most active group is generally from the younger generation known as Generation Y (Gen Y) where their reactions tend to be provocative. The purpose of this paper is to discuss the knowledge and perceptions of Gen Y and Gen X at Universiti Utara Malaysia (UUM) on the Malaysia-Indonesia bilateral relationship and the factors that influence their knowledge and perception. This paper uses quantitative and qualitative methods. The results of the study showed that respondents accepted Indonesia as an important neighbor because of the current state's interests. The cultural and social aspects, particularly audio-visual products such as Indonesian soap operas and Indonesian pop songs have the most significant influence in influencing the respondents' level of knowledge about Indonesia. In addition, they also get a lot of information about Indonesia through electronic media. An important finding from this study is that all respondents acknowledge that Indonesia is still relevant as Malaysia's closest neighbor based on the similarity factor and those good relations between the two countries need to be maintained.